Stochastic analysis of robot-safety systems with common-cause failures - Li, Zhijian (University of Ottawa (Canada), 2003)
This study presents reliability and availability analyses of four different types of robot-safety systems with common-cause failures. The system failure rates and the partially failed system repair rates are assumed constant, and the failed system repair time is assumed arbitrarily distributed. Markov and the supplementary variable methods were used to perform mathematical analysis of these models. Generalized expressions for state probabilities, system availabilities, reliability, mean time to failure, and variance of time to failure are developed. The models developed in this study can be applied to their corresponding robot-safety systems to predict robot-safety system reliability and availability, and to prepare appropriate maintenance scheduling policies.
Keywords: Engineering, Mechanical.